Analisis Kesesuaian Lokasi Produksi Garam Berdasarkan Indeks Kesesuaian Garam (IKG) di Desa Nggolonio, Kabupaten Nagekeo, Nusa Tenggara Timur - Theresia Alvianita Muga; Ima Yudha Perwira; I Wayan Darya Kartika (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2021)
Nggolonio Village is one of the salt production areas in Aesesa District, Nagekeo Regency, East Nusa Tenggara. One effort that can be done to support efforts to increase salt production in Nggolonio Village is to analyze the suitability of salt production locations in the five research locations. The purpose of this study was to determine the Salt Suitability Index in the salt production center in Nggolonio Village. Data was collected in November 2019 from five different locations (three empty sites, one salt farmer area, and one salt company site). To obtain the Salt Suitability Index value, the secondary data was used on this study, such as: rainfall, irradiation time, air humidity, wind speed, air temperature, evaporation rate, and primary data on soil permeability, soil texture, and raw water saturation. The results showed that value of rainfall was 0.2 mm, irradiation time was 9.6 hours/day, air humidity was 31%, wind speed was 7.5 m/s, air temperature was 31 oC, evaporation was 7.8 mm/day, and the soil texture was loam. The soil permeability location I: 1.3×10-3 k, location II: 1.2×10-3 k, location III: 1.3×10-3 k, location IV: 2.0×10-3 k, location V: 1.8×10-3 k, raw water saturation location I: 3.8 oBe, location II: 2.8 oBe, location III: 2.8 oBe, location IV: 3.0oBe, and location V: 2.5 oBe. Based on the results, Salt Suitability Index at five locations in Nggolonio Village has similar index value, namely 88.89 %. These five locations fall into Very Suitable (S1) category as salt production locations.